Faktor-Faktor yang Mempengaruhi Keberhasilan Usaha Mikro Kecil Berbasis Ekonomi Kreatif di Kota Sidoarjo - Eko Winarni; Ali Mahsun (Yos Soedarso Economic Journal (YEJ), 2021)
This study used a quantitative method with the study population being SMEs based on the creative economy in the city of Sidoarjo. The research sample is 100 people from the population. Data collection in this study was carried out using observation techniques, questionnaires, interviews, documentation regarding the factors that influence the success of creative economy-based micro-small businesses in the city of Sidoarjo. The research data were analyzed using multiple linear regression analysis using the SPSS 24 for windows program. The results of this study indicate that the coefficient of interest in entrepreneurship with a coefficient value of 0.075, a network with a coefficient value of 0.110, a brand with a coefficient value, and promotion with a coefficient value of 0.211 using a significant level of 0.05 obtained F count of 3.896 with F table of 3,890, thus F count > F table with a significant level obtained 0.006 <0.05 so that together interest in entrepreneurship, networking, brand promotion influences the success of micro-small businesses based on the creative economy in the city of Sidoarjo. While the rest is influenced by other factors that are not present in this study. Keywords: SMEs; Creative Economy; Businessman.